Theology of Marital Suffering in the Light of Detachment of Saint John of the Cross - Sengkey, Eleine Magdalena; Gunawan, Henricus Pidyarto; Venantius, Supriyono; Obeng, Andrews (Asosiasi Ahli Filsafat Keilahian Indonesia, 2023)
Marital indissolubility is a contentious issue in contemporary Catholic marriages. This qualitative study interviewed eight wives who have endured suffering in their marriages while remaining faithful to the gospel and Church teachings. They viewed their suffering as an ascetic path that leads to spiritual growth. This research explores Saint John of the Cross’s theology of detachment to understand marital suffering. Asceticism within marriage is seen as a means to achieve deeper self-giving to one’s spouse and God. Detachment, a core element of asceticism, purifies one’s being, fostering spiritual growth. John of the Cross’s detachment theology can help couples see their suffering as an avenue to detachment, facilitating divine purification and the ability to transcend marital difficulties without being bound by anything outside of God. This suggests that detachment is a relevant concept in fostering spiritual growth and enhancing self-giving in marriage.